Sosialisasi Tatalaksana dan Teknik Pembuatan Visum et Repertum Di RS PKU Muhammadiyah Gubug Kabupaten Grobogan: Dissemination of Procedures and Techniques for Creating Visum et Repertum at RS PKU Muhammadiyah Gubug, Grobogan Regency - Suyoko; Agiwahyuanto , Faik; Prasetya , Jaka; Abiyasa, Maulana Tomy (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
RS PKU Muhammadiyah Gubug is a Type D hospital with full accreditation, providing Visum et Repertum (VeR) services. In 2022, there were 40 VeR requests for injury cases. However, challenges encountered included incomplete medical record documentation and VeR formats that did not meet the required elements of treatment and care. On January 13, 2023, the Udinus Community Service Team conducted knowledge-sharing sessions, interactive discussions, and mentoring on managing medical information disclosure in the form of VeR. The team also trained 13 medical record staff on creating VeR documents that comply with format requirements and essential elements. These activities involved knowledge sharing and interactive discussions. The results showed that hospital staff enthusiastically participated in the sessions. According to the Head of Medical Records, the team gained understanding and skills in creating standard-compliant VeR, which is expected to improve the quality of VeR services. Continuous mentoring is recommended to address future challenges, enhance the quality of VeR, and optimize service delivery. Keywords: Visum et Repertum, Medical Records, Service Quality